(1125) on the duplication system with repair and preventive maintenance حول نظام النسخ مع الإصلاح والصيانة الوقائية - mohamed, yousif nasr aldin (the institute of national planning, 2018)
two policies for inspection have been considered. in policy i, the operative unit undergoes inspection when its inspection time comes, only if the other unit is in standby state, which will continue the job of the main unit